Synthesis and Characterization of Aluminum Oxide Nanoparticles Prepared by Two Different Cold Plasma Jet Methods - Abdulrhman H. Shaker; Kadhim A. Aadim (Iraqi Journal of Physics)
In this paper, a cold plasma system utilizing a high voltage of 13.5 kV of alternative (AC) and direct current (DC) was used under atmospheric pressure with argon (Ar)-gas at a flow rate of 2.5 l/min and a flowing time of 4 min to synthesize aluminum oxide (AlO) nanoparticles (NP). From the results, when DC was used, it was found that the absorption spectrum starts at 303 nm and gradually falls to 870 nm. With AC, the absorption spectrum was at 330 nm and then began to fall to 902 nm. The energy gap when utilizing DC and AC was 3.49 and 3.44 eV respectively. The analysis of the X-ray diffraction (XRD) patterns showed the structure of the NPs was amorphous, matching the pattern 42-1746. At DC, the average size of NPs formed, as deduced from the XRD pattern, was 29.56 nm, and it was very close to what appeared in the field emission scanning electron microscopy (FESEM) images, in which the apparent NP size ranged between 20 and 50 nm. The XRD test gave an average NP size of 38.21 nm in AC, while the FESEM images showed a size range of 20 - 60 nm. At dc, the AlO NPs were aggregated and interconnected, and each set was connected to another set, as shown in the FESEM images. At AC, the shape of the synthesized AlO NPs was quasi-spherical, with slightly elongated particles connected.